Promoting Public Management Accountability in the Cultural Sector in Brazil - Barroso, Patrick; Araujo, Renata (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2020: Anais do XVI Simpósio Brasileiro de Sistemas de Informação, 2020)
Brazilian public management in the cultural sector has been historically off-balanced, albeit showing some signs of consolidation during President Lula’s government, in the 2000s. During this period, the State enacted several laws to promote public information transparency. Civil Society Organizations of Public Interest (OSCIPs) are Third Sector Organizations (TSOs) which have the prerogative of making agreements with the Brazilian State to carry out public policies, including those in the cultural sector. As government partners, these organizations are also demanded to be accountable to society, being responsive and transparent. However, our research shows this is not the case. We propose the design of accountability mechanisms for these organizations, comprising three artifacts: a conceptual model for OSCIPs for public management in the cultural sector, an information extraction method to collect data from the web based on this model, and an information portal. The research follows the Design Science Research methodology and its results point to the perceived importance of the Portal to cultural business ecosystem.